Ecological and economic implications of alternative metrics in biodiversity offset markets. Issue 5 (13th June 2022) - Simpson, Katherine Hannah; de Vries, Frans P.; Dallimer, Martin; Armsworth, Paul R.; Hanley, Nick
Abstract: Policy tools are needed that allow reconciliation of human development pressures with conservation priorities. Biodiversity offsetting can be used to compensate for ecological losses caused by development activities. Landowners can choose to undertake conservation actions, including habitat restoration, to generate biodiversity offsets. Consideration of the incentives facing landowners as potential biodiversity offset providers and developers as potential buyers of credits is critical when considering the ecological and economic landscape‐scale outcomes of alternative offset metrics. There is an expectation that landowners will always seek to conserve the least profitable land parcels, and, in turn, this determines the spatial location of biodiversity offset credits. We developed an ecological‐economic model to compare the ecological and economic outcomes of offsetting for a habitat‐based metric and a species‐based metric. We were interested in whether these metrics would adequately capture the indirect benefits of offsetting on species not considered under a no‐net‐loss policy. We simulated a biodiversity offset market for a case study landscape, linking species distribution modeling and an economic model of landowner choice based on economic returns of the alternative land management options (restore, develop, or maintain existing land use). Neither the habitat nor species metric adequately captured the indirect benefits of offsetting on related habitats or species. The underlying species distributions, layered with the agricultural and development rental values of parcels, resulted in very different landscape outcomes depending on the metric chosen. If policy makers are aiming for the metric to act as an indicator to mitigate impacts on a range of closely related habitats and species, then a simple no‐net‐loss target is not adequate. Furthermore, to achieve the most ecologically beneficial design of offsets policy, an understanding of the economic decision‐making processes of the landowners is needed. Resumen: Se necesitan herramientas políticas que permitan la reconciliación entre las presiones del desarrollo humano y las prioridades de conservación. La compensación de biodiversidad puede usarse para reponer las pérdidas ecológicas causadas por las actividades de desarrollo. Los terratenientes pueden elegir realizar acciones de conservación, incluyendo la restauración del hábitat, para generar dichas compensaciones. Es importante considerar los incentivos para los terratenientes como proveedores potenciales de compensaciones de biodiversidad y para los desarrolladores como compradores potenciales de créditos cuando se contemplan los resultados ecológicos y económicos a escala de paisaje de estas medidas alternativas de compensación. Existe la expectativa de que los terratenientes siempre buscarán conservar los lotes menos rentables y, por lo tanto, esto determina la ubicación espacial de los créditos por compensación de biodiversidad. Desarrollamos un modelo para comparar los resultados ecológicos y económicos de la compensación en una medida basada en el hábitat y una basada en la especie. Nos interesaba saber si estas medidas indicarían adecuadamente los beneficios indirectos de la compensación para las especies no consideradas bajo una política de pérdida neta cero. Simulamos un mercado voluntario de biodiversidad para un estudio de casode un paisaje, el cual vinculó el modelado de la distribución de especies con el modelo económico de las elecciones de los terratenientes basadas en las ganancias económicas de las opciones alternativas de manejo de suelo (restaurar, desarrollar o mantener el uso de suelo existente). Ninguna de las dos medidas indicó adecuadamente los beneficios indirectos de la compensación para las especies o hábitats relacionados. La distribución subyacente de especies, en conjunto con los valores de renta agrícolas y de desarrollo de los lotes, derivó en resultados muy diferentes de paisaje según la medida seleccionada. Cuando los formuladores de políticas buscan que la medida actúe como un indicador para mitigar impactos en una gama de especies y hábitats relacionados cercanamente, no es adecuado un objetivo simple de pérdida neta cero. Además, para lograr el diseño con el mayor beneficio ecológico, se requiere comprender los procesos de decisión de los terratenientes. 生物多样性补偿市场中替代指标的生态和经济影响: 【摘要】人类发展压力与保护优先事项之间的平衡需要政策工具来调解。生物多样性补偿可以用于弥补发展活动造成的生态损失。土地所有者可以选择采取包括生境恢复在内的保护行动, 来补偿生物多样性的丧失。在评估替代性补偿指标在景观尺度上的生态及经济效益时, 考虑到土地所有者作为潜在的生物多样性补偿提供者和开发者作为潜在的信用购买者所面临的激励措施是至关重要的。一般认为, 土地所有者总是会寻求保护利润最低的地块, 反过来, 这也决定了生物多样性补偿信用的空间位置。本研究开发了一个生态经济模型, 以比较基于生境的指标和基于物种的指标得到的生物多样性补偿的生态和经济结果。我们想探究这些指标是否能充分捕捉到无净损失政策未考虑到的物种在生物多样性补偿中获得的间接利益。为此, 我们模拟了一个案例研究景观中的生物多样性补偿市场, 将物种分布模型与土地所有者基于替代土地管理方案 (恢复、开发或维持现有土地使用) 经济回报做出决策的经济模型相结合, 结果表明, 生境指标和物种指标都不能充分捕捉到生物多样性补偿对相关生境或物种的间接效益。潜在的物种分布加上地块的农业和开发租赁价值, 根据所选指标会导致全然不同的景观结果。如果政策制定者的目标是基于指标评估来减缓对一系列密切相关的生境和物种的影响, 那么简单的无净损失目标是不够的。此外, 为了实现最有利于生态的补偿政策设计, 还需要了解土地所有者的经济决策过程。【翻译: 胡怡思; 审校: 聂永刚】